The caring competencies of nursing students: Comparing the four and two-year Bachelor of Nursing Programme - Sultan, Amir; Sabiha Khanum; Najma Naz; Khan, Sheraz; Sardar Ali; Shakirullah (Journal of the Pakistan Medical Association, 2023)
The study was conducted to determine and compare the caring behaviours of nursing students in four-year BS Nursing (Bachelor of Science in nursing) and two-year Post-RN BSN (Registered nurse to Bachelor of Science in Nursing) programmes. A cross-sectional analytical study was conducted in the nursing institutes of KP from July to September 2022. The sample size was 383 calculated by using the Rao soft sample size calculator. through Caring Behaviour Inventory (CBI-24) having six point Likert scale. Descriptive and inferential statistics were calculated through SPSS 20.0. There were more males, i.e. 60.6%, as compared to female students (39.4%). The overall mean score of caring competencies of Post-RN BS Nursing (Registered nurse to Bachelor of Science in Nursing) was 27.17± 2.17 which is higher than 23.19± 4.1 for BSN students (Bachelor of Science in nursing). Caring behaviours of overall participants are correlated with gender (p-0.001), age (p-0.001), and semester (p-0.001). —Continue